THE EFFECT OF ORGANIZATIONAL CLIMATE AND WORK ENGAGEMENT ON EMPLOYEE JOB SATISFACTION AT THE STATE ASSETS AND AUCTION SERVICE OFFICE (KPKNL) SERANG - Tia Agustin; Khaeruman Khaeruman; Aria Cendana Kusuma (Yayasan Education and Social Center, 2026)
This study aims to analyze the influence of organizational climate and work engagement on employee job satisfaction at the State Assets and Auction Service Office (KPKNL) Serang. The study uses a quantitative approach with a causal associative research design. The study population consisted of 41 employees, all of whom were sampled using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS, supported by instrument tests, classical assumption tests, coefficient of determination tests, partial tests (t-tests), and simultaneous tests (F-tests). The results of the study indicate that organizational climate and work engagement have a positive and significant effect on employee job satisfaction, both partially and simultaneously. Partially, organizational climate obtained a t-value of 5.179, which is greater than the t-table of 2.0243 with a significance value of 0.001 <0.05. In contrast, work engagement obtained a t-value of 2.058, which is greater than the t-table of 2.0243 with a significance value of 0.046 <0.05. Simultaneously, the calculated F value was 24.083, which was greater than the F table of 3.245 with a significance value of 0.001 < 0.05. The results of the study indicate that organizational climate and work engagement together have a significant influence on employee job satisfaction at KPKNL Serang. This finding indicates that the creation of a conducive organizational climate and increasing employee work engagement are important factors in increasing job satisfaction. This study is expected to be a reference for KPKNL Serang in formulating more effective human resource management policies to create a supportive work environment and increase employee job satisfaction.